Thornwaldt cyst - a disease or anomaly - Sotvoldiev Sohibbek Rakhmatullo o'gli; Ashurov Azimjon Mirzazhonovich (Research Parks Publishing LLC, 2020)
Thornwaldt's cyst is a rare congenital pathology characterized by the formation of a pathological cavity (pocket) in the nasopharynx. Discharge accumulates inside such a